2019
DOI: 10.1002/job.2373
|View full text |Cite
|
Sign up to set email alerts
|

Contextual moderators for leadership potential based on trait activation theory

Abstract: Summary This study tested the moderating role of group properties in the relationship between two prototypical leadership attributes (cognitive ability and adjustment) and leadership potential. Building on trait activation theory, we investigated one organizational cue (degree of centralization in the informal social structure) and one social cue (average level of the relevant attribute among other group members) and posited that the two prototypical leadership attributes would more likely be activated (leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 90 publications
(152 reference statements)
1
14
0
Order By: Relevance
“…Thus, trait-relevant situations have the potential to activate people's innate personality traits. Recent empirical evidence provides support for this person-situation interaction consistent with trait activation theory (e.g., Baer et al, 2018;Judge & Zapata, 2015;Klehe et al, 2014;Luria et al, 2019).…”
Section: Interaction Between Self-esteem and Perspective-takingsupporting
confidence: 63%
“…Thus, trait-relevant situations have the potential to activate people's innate personality traits. Recent empirical evidence provides support for this person-situation interaction consistent with trait activation theory (e.g., Baer et al, 2018;Judge & Zapata, 2015;Klehe et al, 2014;Luria et al, 2019).…”
Section: Interaction Between Self-esteem and Perspective-takingsupporting
confidence: 63%
“…Farh et al (2012) demonstrated that the relationship between emotional intelligence and teamwork effectiveness is stronger under a high managerial workload. Luria et al (2019) found that individuals with high cognitive ability, in the context of centralized and hierarchical groups, can earn rewards (in the form of status and popularity) for coming up with creative solutions to problems or helping manage the team; these individuals will then be identified as potential leaders. Below, trait activation theory is applied to propose moderated mediation hypotheses for task complexity.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Second, scholars have devoted scarce attention to the conditions under which transformational leadership influences performance. In fact, from the literature we know that leadership as a human behavior is a function of individual and contextual variables (Luria et al, 2019). Previous studies on leadership theory (e.g., contingency theories) recognize the importance of contextual variables (House & Aditya, 1997).…”
Section: Discussionmentioning
confidence: 99%